A silicon-nanowire memory driven by optical gradient force induced bistability - Yang, Z. C. (2016)
In this paper, a bistable optical-driven silicon-nanowire memory is demonstrated, which employs ring resonator to generate optical gradient force over a doubly clamped silicon-nanowire. Two stable deformation positions of a doubly clamped silicon-nanowire represent two memory states (“0” and “1”) and can be set/reset by modulating the light intensity (<3 mW) based on the optical force induced bistability. The time response of the optical-driven memory is less than 250 ns. It has applications in the fields of all optical communication, quantum computing, and optomechanical circuits.